An Exact Solution of the Second-Order Differential Equation with the Fractional/Generalised Boundary Conditions - Mariusz Ciesielski; Tomasz Blaszczyk (Advances in Mathematical Physics)
We analysed the initial/boundary value problem for the second-order homogeneous differential equation with constant coefficients in this paper. The second-order differential equation with respect to the fractional/generalised boundary conditions is studied. We presented particular solutions to the considered problem. Finally, a few illustrative examples are shown.